2021
DOI: 10.1136/tobaccocontrol-2021-056582
|View full text |Cite
|
Sign up to set email alerts
|

Flavour chemicals, synthetic coolants and pulegone in popular mint-flavoured and menthol-flavoured e-cigarettes

Abstract: BackgroundThe Food and Drug Administration (FDA) has recently banned flavours from pod-style electronic cigarettes (e-cigarettes), except for menthol and tobacco. JUUL customers have quickly discovered that flavoured disposable e-cigarettes from other manufacturers, such as Puff, are readily available. Our goal was to compare flavour chemicals, synthetic coolants and pulegone in mint-flavoured/menthol-flavoured e-cigarettes from JUUL and Puff, evaluate the cytotoxicity of the coolants and perform a cancer risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…In our study design, the administration parameters such as the number of cigarettes smoked, the nicotine content in r-cigs, and/or the frequency of puffing e-cigs were not controlled. Previous studies have reported the variability of the CO levels and/or nicotine concentrations depending on the frequency of puff (Trtchounian et al, 2010), the type of e-cigs (Omaiye et al, 2021), the number of puff duration (Son et al, 2020), and the duration of smoking cigarettes (Ebajemito et al, 2020). In our study, participants were allowed to smoke r-cigs or to vape e-cigs until their nicotine craving were satiated, and this might have caused the variability in the nicotine exposure.…”
Section: Discussionmentioning
confidence: 90%
“…In our study design, the administration parameters such as the number of cigarettes smoked, the nicotine content in r-cigs, and/or the frequency of puffing e-cigs were not controlled. Previous studies have reported the variability of the CO levels and/or nicotine concentrations depending on the frequency of puff (Trtchounian et al, 2010), the type of e-cigs (Omaiye et al, 2021), the number of puff duration (Son et al, 2020), and the duration of smoking cigarettes (Ebajemito et al, 2020). In our study, participants were allowed to smoke r-cigs or to vape e-cigs until their nicotine craving were satiated, and this might have caused the variability in the nicotine exposure.…”
Section: Discussionmentioning
confidence: 90%
“…Since these synthetic coolants are either more potent or comparable TRPM8 agonists to menthol, it is likely they facilitate inhalation in vapers using the products analyzed by us. One recent study also quantified menthol and the synthetic coolants (WS-3 and WS-23) in Puffbar devices 15 . This study (Omaiye et al,) found similar quantities of synthetic coolants and a higher quantity of menthol in the Puffbar “Cool Mint” product, and higher quantities of all 3 compounds in the “Menthol” product 15 .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study also quantified menthol and the synthetic coolants (WS-3 and WS-23) in Puffbar devices 15 . This study (Omaiye et al,) found similar quantities of synthetic coolants and a higher quantity of menthol in the Puffbar “Cool Mint” product, and higher quantities of all 3 compounds in the “Menthol” product 15 . Some of these differences in amounts could be that, the tested “Cool Mint” device in this study was smaller in size (1.3 mL) than what was analyzed in Omaiye et al, study (3.2 mL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations